Teori Kebenaran Pancasila sebagai Dasar Pengembangan Ilmu - Budisutrisna, Budisutrisna (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
Science, by its method, wants to get truth. Science is a humancreation; the truth does not only to fulfill correspondence-coherencecriteria of truth, induction-deduction, and empirical-rationalthought. The truth and science developing in Indonesia also mustbe back to mankind, Indonesian identity. Pancasila theory of truthconsists of correspondence, coherence, and pragmatic that all ofthose are complemented simultaneously in scientific work. Thedeveloping of science in Indonesia must be based on Pancasilavalues. For Pancasila, the scientific truth must coherent to god,humanity, one, people, and justice values.